Low cost flat: A study on comfort level in relation on design and planning / Nordiana Ahyad - Ahyad, Nordiana (2001)
Comfortable is the important thing for occupant lives n their house. Living in high density more exposed to comfortable problem due to occupant’s complaint especially living in low cost flat. Comfortable living can be related to design development for the house. In Malaysia, the Malaysian Government has targeted to built 235,000 units of low cost houses. There is no research in Malaysia has been done on the design comfort of low cost flat especially for three major ethnic groups namely Malay, Chinese and Indian with each groups’ own culture and lifestyle. This study present on design comfort for low cost flat developed by government and private sector. It included correct orientation of the building, layout of units according to prevalent wind direction, cross ventilation, temperature, lighting and noise.